MicroRNA-21 Limits Macrophage Responses to Mycobacterium tuberculosis - HACKETT, EMER (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2019)
Mycobacterium tuberculosis (Mtb) is an intracellular pathogen that subverts the innate immune response. The Mtb pandemic is of global concern. Emerging strains of antibiotic-resistant Mtb warrant the development of host-directed therapies and improved vaccination strategies. The macrophage is the primary host cell for Mtb and understanding how the bacterium co-opts this immune cell as a survival niche is of vital importance. Increased glycolysis is an essential process driving host defence against Mtb, but little is known about how metabolism is regulated during infection. MicroRNA-21 (miR-21) is a putative negative regulator of TLR signalling induced to promote immunoregulatory responses, but its role during Mtb infection has not been described.? This work describes a novel role for miR-21 during Mtb infection in the manipulation of metabolic reprogramming. The findings of this work illustrate that miR-21 is induced by Mtb infection and upregulation of miR-21 coincides with the switch from a pro-inflammatory to an immunoregulatory macrophage permissive to bacterial replication. This overlaps with negative regulation of metabolic reprogramming. Blocking miR-21 increases bacterial containment via increased pro-inflammatory mediators including IL-1. This increase in IL-1 is dependent on enhanced glycolysis, demonstrating that miR-21 negatively regulates immune activation by limiting metabolic reprogramming. This work also describes the mechanism by which miR-21 limits glycolysis, describing a new target at the committed step of glycolysis, namely one isoform of the phosphofructokinase 1 enzyme - PFK-M. Unlike other glycolytic genes and PFK isoforms, PFK-M expression is repressed during Mtb infection. This repression limits glycolysis and pro-inflammatory responses, however an immune activating signal from IFN- can override this brake on immunometabolic reprogramming. IFN- post-transcriptionally limits miR-21 expression, thus relieving the repression of PFK-M and permitting full macrophage activation in response to Mtb. This dual targeting of this pathway by miR-21 and targeting of miR-21 by IFN- highlight the central importance of immunometabolism to the immune response. By describing a novel level of regulation of the glycolytic machinery by miR-21, modulated by both host & pathogen responses, these findings open new avenues for targeting immunity in infection as well as other diverse diseases including metabolic syndrome & cancer.
APPROVED
Keywords: microRNA; macrophage; mycobacterium tuberculosis; metabolism; mir-21; PFK-M